Grundtvigs vej til de Norrøne skrifter - Albeck, Gustav (Grundtvig-studier, 1953)
How Grundtvig Found His Way to the leelandie Manuseripts .By Gustav Albeek.In his hook "Grundtvig som filolog" Helge Toldberg has suggested that Grundtvig found his way indepently to the old Nothern (Icelandic) language, and it was he who led the friend of his youth, P. N. Skovgaard, to the old Northem litterature, these important sources of the history and mythology of the Ancient North.This is, however, in conflict with what Grundtvig him self says of his relations with Skovgaard, as he depicts them at different periods in his life. An analysis of the contemporary source material, and chiefly of Grundt vig's diaries and !etters, also shows that Toldherg's thesis is incorrect. In his youth Grundtvig was not interested in the study of sources. He was simply seeking material for his poetry and his mythological speculations, and was getting advice all the time from Skovgaard, who knew much more about the subject. Only gradually did Grundtvig find himself forced into taking up a real study of the sources and learning Old lcelandic. During his last year on Langeland - 1807-8 - he became aware -thanks again to Skovgaard - of the necessity of studying the Mss. In conseqvence of the war with England, these could not be sent to Langeland. Grundtvig's departure from the island in April, 1808, was therefore also hastened by his growing desire to get to work on the study of the ancient Mss. in Copenhagen. Skovgaard, however , having come under the ban of the litterary Censorship, had to give up his studies and leave Cophenhagen, while his pupil, Grundtvig, was able to con tinue his studies and win himself international fame for his studies of manu script sources (especially his work on Beawulf).